Pandora’s Box of Food Estate: An Examination of Food Securitization in Jokowi’s Second Term Through Just Securitization Theory - Rafi Faishal Akbar; Wishnu Mahendra Wiswayana (International Journal Labs, 2025)
This research investigates the securitization of food in Indonesia through the Food Estate program implemented during President Joko Widodo’s second term (2019–2024), with a focus on pilot projects in Central Kalimantan and North Sumatra. Using Rita Floyd’s Just Securitization Theory (JST) as the analytical framework, the study assesses the ethical legitimacy of the securitization process by examining its initiation, conduct, and termination. Employing a qualitative, case study-based approach and analyzing secondary data from government reports, NGO findings, and academic literature, the research reveals that the Food Estate program fails to meet all three JST criteria. Despite being justified by the COVID-19 crisis, data showed no actual rice shortages, undermining the claim of an existential threat. The conduct of the program marginalized indigenous communities, bypassed environmental regulations, and prioritized corporate interests over local needs, violating principles of proportionality and human rights. Furthermore, the program has continued to expand even after the pandemic’s end, without plans for desecuritization or restoration, violating JST’s just termination principle. The findings contribute to securitization scholarship by pioneering the application of JST to food policy and illustrating how securitization can entrench elite interests and bypass democratic governance. The study calls for institutional safeguards, indigenous inclusion, and environmental accountability in future food resilience strategies to prevent the misuse of emergency rhetoric for long-term political and economic gain.